ChemInform Abstract: Efficient Click‐Polymer‐Stabilized Palladium Nanoparticle Catalysts for Suzuki—Miyaura Reactions of Bromoarenes and Reduction of 4‐Nitrophenol in Aqueous Solvents. Issue 15 (15th April 2014) - Deraedt, Christophe; Salmon, Lionel; Ruiz, Jaime; Astruc, Didier
Abstract Palladium nanoparticles (size=1.6.+‐.0.3 nm) used for the Suzuki—Miyaura coupling of aryl bromides with phenyl boronic acid are stabilized by polyethylene glycol containing triazolyl rings synthesized by click reaction in water.